1999
DOI: 10.1159/000056523
|View full text |Cite
|
Sign up to set email alerts
|

Summary Report of the TD-3 Workshop: Characterization of 83 Antibodies against Prostate-Specific Antigen

Abstract: Twelve research groups participated in the ISOBM TD-3 Workshop in which the reactivity and specificity of 83 antibodies against prostate-specific antigen (PSA) were investigated. Using a variety of techniques including cross-inhibition assays, Western blotting, BIAcore, immunoradiometric assays and immunohistochemistry, the antibodies were categorized into six major groups which formed the basis for mapping onto two- and three-dimensional (2-D and 3-D) models of PSA. The overall findings of the TD-3 Workshop a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 37 publications
0
42
0
1
Order By: Relevance
“…PSA was immobilized to the solid phase by mAb H117 which binds to the same epitope as mAb 5E4 [29]. The capture antibody was covalently coupled onto the surface of the CM5 sensor chip according to the manufacturer's instructions, using coupling levels of 5000 resonance units (RU).…”
Section: Surface Plasmon Resonancementioning
confidence: 99%
See 1 more Smart Citation
“…PSA was immobilized to the solid phase by mAb H117 which binds to the same epitope as mAb 5E4 [29]. The capture antibody was covalently coupled onto the surface of the CM5 sensor chip according to the manufacturer's instructions, using coupling levels of 5000 resonance units (RU).…”
Section: Surface Plasmon Resonancementioning
confidence: 99%
“…For characterization of the binding site of the peptides on PSA, monoclonal anti PSA antibodies recognizing various epitopes on PSA were used [29]. Each mAb (33 nm) was incubated in wells containing PSA bound by mAb 5E4.…”
mentioning
confidence: 99%
“…15,40,41 In the present study, the specific targeting of fPSA was investigated by using PSA30, an IgG1 that is specific for an epitope region uniquely available on fPSA alone. 30,32 We successfully employed labeling with 125 I and evaluated targeting by DAR and biodistribution studies in both LNCaP-tumor-bearing mice and nontumor-bearing animals. The uptake of 125 I-PSA30 on DAR was compared with the uptake of co-injected 18 F-labeled metabolic probes (FDG and choline).…”
Section: Discussionmentioning
confidence: 99%
“…31 Comprehensive epitope mapping studies have demonstrated that PSA30 has very similar binding characteristics to some of the originally developed mouse mAbs (e.g., 5A10) specific for fPSA alone, 17,19,30,32 and PSA30 recognizes an epitope covered by ACT that is accessible only on fPSA.…”
Section: The Psa30 Mabmentioning
confidence: 96%
“…For proteins, reference methods typically will require well-characterized antibodies. The establishment of an epitope map for PSA has facilitated development of assays that measure free and complexed PSA equally (8 ). The epitopes recognized by many hK2 antibodies have already been characterized (9 ), and it is to be hoped that the authors extend these studies by mapping all available antibodies.…”
mentioning
confidence: 99%